2012
DOI: 10.1177/1534735412450513
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 3-Week Intervention of Shi Quan Da Bu Tang for Alleviating Hematotoxicity Among Patients With Breast Carcinoma Receiving Chemotherapy

Abstract: Purpose. Although Shi Quan Da Bu Tang (SQDBT) has been used to treat cancer patients clinically, very few studies evaluating the effectiveness of SQDBT using objective indicators have been published. The study objectives were to examine the effectiveness of SQDBT for alleviating hematotoxicity, as indicated by white blood cell (WBC) counts and hemoglobin (Hb) levels, among patients with breast carcinoma receiving chemotherapy. Methods. The authors identified patients with breast carcinoma who received chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…JTT (Shi-Quan-Da-Bu-Tang in Chinese) is an immunostimulatory herbal formulation with an ideal balance of safety and efficacy [1,2]. In East Asia, the formulation has been used clinically for immunocompromised individuals, such as cancer patients undergoing chemotherapy and radiation [1][2][3][4]. JTT stimulates various leukocytes, including T, B, and NK cells and MΦ, which result in antitumor and anti-metastatic effects as well as alleviation of anemia and leukopenia [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…JTT (Shi-Quan-Da-Bu-Tang in Chinese) is an immunostimulatory herbal formulation with an ideal balance of safety and efficacy [1,2]. In East Asia, the formulation has been used clinically for immunocompromised individuals, such as cancer patients undergoing chemotherapy and radiation [1][2][3][4]. JTT stimulates various leukocytes, including T, B, and NK cells and MΦ, which result in antitumor and anti-metastatic effects as well as alleviation of anemia and leukopenia [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…15 JTT is used clinically in East Asia to strengthen the immune functions of patients with various diseases, including cancer, 16,17 hepatitis C, 18 and otitis. 19 The formulation is a mixture of ten different herbs (see Table S1 in Supplementary data).…”
mentioning
confidence: 99%
“…Traditional chemotherapeutics often causes hematotoxicity when administrated against cancer (Lin et al, 2010;Huang et al, 2013). In the present study, we found that cecropin treatment had no influence on hematological phenotype including Hb content, WBC and RBC count, as well as PCV in BEL-7402 tumor-beared mice as compared with saline treatment.…”
Section: Discussionmentioning
confidence: 45%